2015
DOI: 10.1002/jrs.4654
|View full text |Cite
|
Sign up to set email alerts
|

SERS detection of polychlorinated biphenyls using β-cyclodextrin functionalized gold nanoparticles on agriculture land soil

Abstract: A highly sensitive surface-enhanced Raman scattering (SERS) platform for the selective trace analysis of persistent organic pollutant (POP) such as polychlorinated biphenyl (PCBs) was reported based on β-CD modified gold nanoparticles (AuNPs) with the real environmental sample of polluted soil. The synthesized gold nanoparticles were characterized using UV-vis spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and transmission electron microscopy (TEM). In polluted soil the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The value is different from what it would be in the general solution phase, which is a 420 nm UV absorbance from 30 nm Ag NPs. This discrepancy may stem from different synthesis and measurement conditions used in this study [ 37 , 38 , 39 ]; the Ag NPs were synthesized by UV irradiation (at 254 nm) without adding a stabilizer and the Ag NPs were measured under dry conditions. The absorption band of Ag NPs is matched with the dye.…”
Section: Resultsmentioning
confidence: 99%
“…The value is different from what it would be in the general solution phase, which is a 420 nm UV absorbance from 30 nm Ag NPs. This discrepancy may stem from different synthesis and measurement conditions used in this study [ 37 , 38 , 39 ]; the Ag NPs were synthesized by UV irradiation (at 254 nm) without adding a stabilizer and the Ag NPs were measured under dry conditions. The absorption band of Ag NPs is matched with the dye.…”
Section: Resultsmentioning
confidence: 99%
“…Arockia Jency and co‐workers used SERS to detect polychlorinated biphenyls using β‐cyclodextrin functionalized gold nanoparticles on agriculture land soil. They found that when contaminated soil was added to the system, the binding of soil with β‐CD resulted in the aggregation of AuNPs, and excellent Raman signal was obtained which can reflect the isomers of polychlorinated biphenyls . Dhara et al .…”
Section: Nanomaterialsmentioning
confidence: 99%
“…High sensitivity in PCB detection, up to 10 − 6 -10 − 7 M, was reported for conventional plasmonic SERS substrates in the absence of receptors [13][14][15][16][17]. However these approaches can be utilized only in lab-scale experiments as they do not allow for a direct capture of PCBs in water under real world conditions.…”
mentioning
confidence: 99%